New record of Hydrozoa Distichopora violacea (Pallas, 1766) (Anthoathecata: Stylasteridae) from Andaman and Nicobar Islands, India - Chakraborty, Oishinee; Raghunathan, C.; Chandra, Kailash (Zootaxa, 2018)
The class Hydrozoa consists of mostly marine and few freshwater organisms classified into 7 orders amongst which the order Anthoathecata consists of 48 families with approximately 1,140 valid species (Cartwright & Collins 2007). Stylasteridae is one among the families that comprises the order Anthoathecata, and is characterized by a calcareous exoskeleton which is often brightly pigmented. The members of the family are commonly called lace corals. They are usually small in size and commonly found in crevices and caves in coral reef areas.